2008
DOI: 10.1083/jcb.200710107
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated Nav channel targeting in the heart requires an ankyrin-G–dependent cellular pathway

Abstract: Voltage-gated Nav channels are required for normal electrical activity in neurons, skeletal muscle, and cardiomyocytes. In the heart, Nav1.5 is the predominant Nav channel, and Nav1.5-dependent activity regulates rapid upstroke of the cardiac action potential. Nav1.5 activity requires precise localization at specialized cardiomyocyte membrane domains. However, the molecular mechanisms underlying Nav channel trafficking in the heart are unknown. In this paper, we demonstrate that ankyrin-G is required for Nav1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 84 publications
3
141
1
1
Order By: Relevance
“…31,32 Ankyrin-G is primarily expressed at the intercalated discs, with another population at T-tubules; it is therefore unlikely that it is responsible for the specific targeting of Na v 1.5 to the 2 compartments observed in our study. Whether the roles of syntrophin-dystrophin and ankyrin-G in trafficking, targeting, and anchoring of Na v 1.5 to the lateral membrane are complementary or partly redundant remains to be elucidated.…”
Section: Physiological Relevance Of the Two Regulating Mechanismsmentioning
confidence: 63%
“…31,32 Ankyrin-G is primarily expressed at the intercalated discs, with another population at T-tubules; it is therefore unlikely that it is responsible for the specific targeting of Na v 1.5 to the 2 compartments observed in our study. Whether the roles of syntrophin-dystrophin and ankyrin-G in trafficking, targeting, and anchoring of Na v 1.5 to the lateral membrane are complementary or partly redundant remains to be elucidated.…”
Section: Physiological Relevance Of the Two Regulating Mechanismsmentioning
confidence: 63%
“…Ankyrin-G has been shown to play a role in the trafficking and anchoring of the cardiac sodium channel Nav1.5 (244,285), and, similar to that channel, ankyrin-G is also expressed at the intercalated discs and in the t-tubules of adult myocytes (283). Lowe et al (244) have shown that reduction of ankyrin-G expression in cardiac myocytes leads to reduced sodium currents and lowered Nav1.5 expression.…”
Section: Ankyrinsmentioning
confidence: 99%
“…Lowe et al (244) have shown that reduction of ankyrin-G expression in cardiac myocytes leads to reduced sodium currents and lowered Nav1.5 expression. This effect was specific for the ankyrin-G isoform, as this reduction was not observed in myocytes with reduced expression of ankyrin-B.…”
Section: Ankyrinsmentioning
confidence: 99%
“…Furthermore, mice deficient in β IV -spectrin display defects in neuronal Na + channel clustering and function (29). In heart, ankyrin-G targets voltage-gated Na + channels (Na v 1.5) to the intercalated disc (43,44), and cardiac Na + channel membrane regulation has been associated with CaMKII activity (16). We therefore tested whether the β IV -spectrin/CaMKII complex formed a macromolecular complex with ankyrin-G and Na v 1.5 in heart.…”
Section: Introductionmentioning
confidence: 99%